2021
DOI: 10.3390/ijms23010056
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Foam Rafts Supported In Vitro Cultures of Rindera graeca Roots for Enhanced Production of Rinderol, Potent Proapoptotic Naphthoquinone Compound

Abstract: Unique phytochemical profile of plants belonging to Boraginaceae family provides a prolific resource of lipophilic pigments from the group of naphthoquinone derivatives. To overcome low compound content, the major obstacle of plant-based production, immobilization of Rindera graeca roots in in vitro cultures was implemented for efficient production of rinderol, novel furanonaphthoquinone derivative with anticancer properties. Chromatographic procedures revealed rinderol presence in extracts of all investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Authors suggest that in specific culture conditions, in LBA and shikonin biosynthetic pathway, in which they share its early steps, the phenylpropanoid unit is further favorably used for LBA synthesis. Nevertheless under conditions of this study in two samples of 28-day old roots: RgAR and hairy of RgTR17 line was detected rinderol, a furano-naphthoquinone compound demonstrating antiapoptotic potential [13]. Previously rinderol was determined both in RgTR7 and RgTR17 28-old-day root lines cultivated in vitro [11], but in further subcultures its biosynthesis was induced only in cultures carried out on polyurethane rafts [11].…”
Section: Hplc-pda-esi-hrms Analysismentioning
confidence: 67%
See 1 more Smart Citation
“…Authors suggest that in specific culture conditions, in LBA and shikonin biosynthetic pathway, in which they share its early steps, the phenylpropanoid unit is further favorably used for LBA synthesis. Nevertheless under conditions of this study in two samples of 28-day old roots: RgAR and hairy of RgTR17 line was detected rinderol, a furano-naphthoquinone compound demonstrating antiapoptotic potential [13]. Previously rinderol was determined both in RgTR7 and RgTR17 28-old-day root lines cultivated in vitro [11], but in further subcultures its biosynthesis was induced only in cultures carried out on polyurethane rafts [11].…”
Section: Hplc-pda-esi-hrms Analysismentioning
confidence: 67%
“…These studies revealed the presence of phenolic compounds, pyrrolizidine alkaloids, naphthoquinone shikonin-type compounds and among them rinderol, a potent cytotoxic agent [7,11,12]. Rinderol production was optimized in root cultures of R. graeca and its proapoptotic activity was demonstrated [13]. Other various biological activities were also reported for plants of Rindera genus, including antiinflammatory [14], anti-viral [15], and antimicrobial attributed to the presence of essential oils distilled from aerial part [16], in addition the latter were also demonstrated for methanolic and hexane extracts of shoots and hairy roots of R. graeca cultivated in vitro as well as rinderol [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Rindera graeca hairy roots were originally introduced to the in vitro conditions and were established as a stable culture by Katarzyna Sykłowska-Baranek et al [ 43 ]. Before the developing culture systems supported with samples of xerogels, the inoculum of R. graeca hairy roots was maintained in 250 mL Erlenmeyer flasks filled with 50 mL of hormone-free DCR medium (PhytoTech Labs, Inc., Lenexa, KS, USA) [ 14 ]. The flasks were agitated on an oscillatory shaker ISS-7100 (Lab Companion, Billerica, MA, USA) at 105 rpm and 24 °C in darkness for 28 days.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the unique but end-user-defined parameters of a strictly controlling bioprocess environment allow for various culture system modifications. Among reported techniques, much attention is dedicated to in situ separation of bioproducts, defined as a process of directed metabolite accumulation within an additional phase (i.e., liquid extractant or solid-state adsorbent) added into the culture medium [ 13 , 14 , 15 ]. The desired selectivity of in situ applied extractant/adsorbent toward a specific metabolite is favorable for production efficiency because it enables enhanced secretion of bioproducts through its selective separation from the culture medium, resulting in the cancellation of separated metabolite biosynthesis inhibition, which finally resulted in increased yield of its production [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…New extraction methods, including ultrasonic-assisted extraction [28][29][30], supercritical fluid extraction [29][30][31], and accelerated solvent extraction [32], are fast and efficient for extracting chemicals from plant matrices. In addition, in situ extraction is considered an efficient method to recover secondary metabolites; moreover, it allows both to improve the yield of the product and to orient the secondary metabolite pathway's in vitro culture system [33][34][35]. As the results revealed, the use of perfluorodecalin in the in situ extraction system improved the performance of the cells' culture as well as increased the production of targeted molecules [36,37].…”
Section: Introductionmentioning
confidence: 99%